Influenza but not pneumococcal vaccination protects against all-cause mortality in patients with COPD. Issue 7 (24th March 2009) - Schembri, S; Morant, S; Winter, J H; MacDonald, T M
Abstract : Background: Influenza and pneumococcal vaccination are recommended in patients with chronic obstructive pulmonary disease (COPD). A recent study from Tayside found a reduced risk of all-cause mortality with vaccination in patients with COPD. The Health Improvement Network (THIN) database was used to test this hypothesis in a different data source. Methods: The THIN database was searched for patients with COPD. Vaccination status against Pneumococcus and the annual influenza vaccination status were determined. Mortality rates were calculated in the periods December to March and April to November. Relative risks for the effect of vaccination on all-cause mortality were estimated by Poisson regression, adjusting for age, sex, year and serious co-morbidities. Results: 177 120 patients with COPD (mean age 65 years) were identified, with a mean follow-up of 6.8 years between 1988 and 2006. Vaccination rates against influenza rose from <30% before 1995 to >70% in 2005 in patients aged 60 years or more. The cumulative vaccination rate against pneumonia rose from almost zero to 70% in patients aged 70 years or more over the same period. For all-cause mortality the adjusted relative risks associated with influenza vaccination were 0.59 (95% CI 0.57 to 0.61) during the influenza season and 0.97 (95% CI 0.94 to 1.00) outside the season in patients not vaccinated against pneumonia, and 0.30 (95% CI 0.28 to 0.32) and 0.98 (95% CI 0.96 to 1.11), respectively, in patients vaccinated against pneumonia. The relative risk associated with pneumococcal vaccination was >1 at all times of the year. Conclusions: Influenza but not pneumococcal vaccination was associated with a reduced risk of all-cause mortality in COPD.